STRATEGIES USED BY MOTHERS WHOSE CHILDREN HAVE HIV, FOR CO-EXISTING WITH THE DISEASE - Marli Teresinha Gimeniz Galvão; Ivana Cristina Vieira Lima; Gilmara Holanda da Cunha; Vanessa Frota Santos; Maria Isabella Aguiar Mindêllo (Universidade Federal do Paraná, 2013)
The aim was to identify strategies used by mothers whose children have HIV, so as to co-exist with the disease. It is a qualitative study undertaken between February and March 2011 in a public hospital which is a center of excellence in care for individuals with HIV and AIDS, in Fortaleza-Ceará. Ten HIV-positive mothers with at least one child with HIV-positive serology, participated in an interview with a semi-structured script. The data was submitted to thematic content analysis, producing five categories: Adoption of religiosity as a source of hope; Strengthening of the care for the child, and over-protection; Search for family and social support; Development of self-blame; Denial of the illness and concealment of the diagnosis. The results show that the mothers find positive and negative strategies for coping with the disease. Nursing can contribute to the integration of the family members of people with HIV and provide a better quality of life, in accordance with the resources which these have to live.